(untitled) (Global Journal of Science Frontier Research, 2023)
Two worldwide events opened novel reflections in a highly vast scientific literature concerning a universal concept like that of data namely as the results of observations either experimental or human-mind generated the big data and the universal use of informatics related to each other and both in exponential increase The capacity and speed of modern computers allowed us obtaining such immense amounts of data both from experimental setups or from the elaboration of algorithms either human-built or through AI Their handling too is necessarily operated via informatics means considered distinct from mathematical means Apparently these facts have disconnected data evaluation from traditional fields not only science but also the way to take decisions based on them The paper contains reflections on the properties and meaning of the data in their-self specifically as the vehicle of information almost universally necessary to make decisions the latter being a frame that is mixed and often prevalent in the literature about big data